Novelty seeking is associated with increased body weight and orbitofrontal grey matter volume reduction. (April 2021) - Ludwig, Marius; Richter, Maike; Goltermann, Janik; Redlich, Ronny; Repple, Jonathan; Flint, Claas; Grotegerd, Dominik; Koch, Katharina; Leehr, Elisabeth J.; Meinert, Susanne; Hülsmann, Carina; Enneking, Verena; et al.
Abstract: Novelty seeking (NS) has previously been identified as a personality trait that is associated with elevated body mass index (BMI) and obesity. Of note, both obesity and reduced impulse control – a core feature of NS – have previously been associated with grey matter volume (GMV) reductions in the orbitofrontal cortex (OFC). Yet, it remains unknown, if body weight-related grey matter decline in the OFC might be explained by higher levels of NS. To address this question, we studied associations between NS, BMI and brain structure in 355 healthy subjects. Brain images were pre-processed using voxel-based morphometry (VBM). BMI was calculated from self-reported height and weight. The Tridimensional Personality Questionnaire (TPQ) was used to assess NS. NS and BMI were associated positively ( r  = .137, p  = .01) with NS being a significant predictor of BMI ( B  = 0.172; SE B  = 0.05; ß  = 0.184; p  = 0.001). Significant associations between BMI and GMV specifically in the OFC (x = −44, y = 56, z = −2, t (350) = 4.34, k  = 5, p FWE = 0.011) did not uphold when correcting for NS in the model. In turn, a significant negative association between NS and OFC GMV was found independent of BMI (x = −2, y = 48, z = −10, t (349) = 4.42, k  = 88, p FWE = 0.008). Body mass-related grey matter decrease outside the OFC could not be attributed to NS. Our results suggest that body-weight-related orbitofrontal grey matter reduction can at least partly be linked to higher levels of NS. Given the pivotal role of the OFC in overweight as well as cognitive domains such as impulse inhibition, executive control and reward processing, its association with NS seems to provide a tenable neurobiological correlate for future research. Highlights: We investigated associations between novelty seeking, BMI and brain structure in 355 healthy participants. We found that novelty seeking is linked to BMI and body-weight-related grey matter decrease in the orbitofrontal cortex. Novelty seeking and associated orbitofrontal grey matter volume may provide a neurobiological correlate of increased BMI.